Dysfunctional family environment in affected versus unaffected offspring of parents with bipolar disorder. (November 2013) - Ferreira, Guilherme S; Moreira, Carolina RL; Kleinman, Ana; Nader, Edmir CGP; Gomes, Bernardo Carramão; Teixeira, Ana Maria A; Rocca, Cristiana C Almeida; Nicoletti, Mark; Soares, Jair C; Busatto, Geraldo F; Lafer, Beny; Caetano, Sheila C
Objective: Children of parents with bipolar disorder (BD) are at heightened risk for developing mood and other psychiatric disorders. We proposed to evaluate the environment of families with at least one parent with BD type I (BDF) with affected offspring (aBDF) and unaffected offspring (uBDF) compared with control families without a history of DSM-IV Axis I disorder (CF). Method: We used the Family Environment Scale (FES) to evaluate 47 BDF (aBDF + uBDF) and 30 CF. Parents were assessed through the Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I). Diagnosis of the offspring was determined through the Schedule for Affective Disorders and Schizophrenia for School-Age Children/Present and Lifetime Version (K-SADS-PL) interview. Results: There were statistically significant differences between aBDF, uBDF and CF in cohesion ( p = 0.003), intellectual-cultural orientation ( p = 0.01), active-recreational orientation ( p = 0.007), conflict ( p = 0.001), control ( p = 0.01), moral-religious emphasis ( p = 0.01) and organization ( p = 0.001). The aBDF showed higher levels of control ( p = 0.02) when compared to the uBDF. Conclusions: Families with a BD parent presented more dysfunctional interactions among members. Moreover, the presence of BD or other psychiatric disorders in the offspring of parents with BD is associated with higher levels of control. These results highlight the relevance of psychosocial interventions to improve resilience and family interactions.